Cross-section of (n, 2n) reaction for niobium and strontium isotopes between 13.97 to 20.02 MeV neutron energies. (April 2022) - Mehta, Mayur; Singh, N.L.; Singh, Ratankumar; Chauhan, Rakesh; Makwana, Rajnikant; Suryanarayana, S.V.; Naik, H.; Subhash, P.V.; Mukherjee, S.; Varmuza, Jan; Katovsky, Karel
Abstract: The activation cross-sections of 93 Nb(n, 2n) 92 Nb m and 88 Sr(n, 2n) 87 Sr m reactions were measured using the activation and off-line γ-ray spectrometry technique in the neutron energy range 13.97–20.02 MeV. The present measurements have been done at the neutron energies where there are deficiencies and scarcity in the reaction cross-section data. The neutron flux was determined using the 27 Al(n, α) 24 Na monitor reaction. The γ-ray self-attenuation effect and the low energy background neutron corrections were done in this experiment. The results of the present work were compared with the previously published data and evaluated nuclear data libraries. Theoretically, the cross-section for 93 Nb(n, 2n) 92 Nb m and 88 Sr(n, 2n) 87 Sr m reactions was predicted by TALYS-1.9 nuclear code and compared with the present results. Highlights: The cross-section of 93 Nb(n, 2n) 92 Nb m and 88 Sr(n, 2n) 87 Sr m reactions were measured in 13.97 to 20.02 MeV neutron energy range. The comparisons of present results were done with previously published data, evaluated data and theoretically predicted data by TALYS-1.9 code. The experimental results are in good agreement with the previously published data and are following trend line of evaluated data. This work filled the gap in cross-sections data for both the reactions.